2010
DOI: 10.1007/s10641-010-9622-0
|View full text |Cite
|
Sign up to set email alerts
|

Physiological stress response of Mountain Whitefish (Prosopium williamsoni) and White Sucker (Catostomus commersoni) sampled along a gradient of temperature and agrichemicals in the Oldman River, Alberta

Abstract: Species differences in tolerance to environmental stressors can contribute to differences in species distribution and abundance along river gradients. Climate change and intensive agriculture are likely to have major effects on fish populations in temperate zones, yet understanding of the interactions between temperature and chemical stressors on fish physiology is limited. The objective of this study was to compare the stress responses of the Mountain Whitefish, (Prosopium williamsoni, a cold-water fish) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Interestingly, events such as drought are known to trigger stress responses in many vertebrate species (Baker et al, 2013;Jessop et al, 2003;Tokarz and Summers, 2011;Wikelski et al, 2001). Variation in water temperature is another environmental variable that should be considered when studying wild fish, since several authors have demonstrated its influence on cortisol stress responses (Blevins et al, 2012;Cook et al, 2011;Meka and McCormick, 2005;Quinn et al, 2010). In order to cope with subtle changes in the environment, such as the above mentioned, healthy individuals are predicted to increase GC secretion (Wikelski and Cooke, 2006), leading to higher circulating cortisol levels (Bonier et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, events such as drought are known to trigger stress responses in many vertebrate species (Baker et al, 2013;Jessop et al, 2003;Tokarz and Summers, 2011;Wikelski et al, 2001). Variation in water temperature is another environmental variable that should be considered when studying wild fish, since several authors have demonstrated its influence on cortisol stress responses (Blevins et al, 2012;Cook et al, 2011;Meka and McCormick, 2005;Quinn et al, 2010). In order to cope with subtle changes in the environment, such as the above mentioned, healthy individuals are predicted to increase GC secretion (Wikelski and Cooke, 2006), leading to higher circulating cortisol levels (Bonier et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples from ten fish were taken from four sites along the elevational gradient [a Crowsnest R tributary 1234 m, two Racehorse Creek tributaries (1478 and 1539 m), and the Oldman River mainstem (1722 m)] in July 2006. Plasma AchE activity [(µmol min) ml −1 ], liver glycogen, plasma glucose and cortisol, and gill Na + /K + ATPase activity were measured in tissue and blood samples from these fish (Chuiko, 2000; Levesque et al ., 2002, 2003; Quinn, Rasmussen & Hontela, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The exact mechanisms for declines are often unknown. Studies have documented mechanisms of Mountain Whitefish mortality including whirling disease (Schisler 2010;Pierce et al 2012), high temperatures (Boyd 2008;Brinkman et al 2013), pollutants (Brinkman et al 2008;Quinn et al 2010), decreased discharge, and entrainment (Kennedy 2009). However, little is known about the effects of these stressors on populations (but see IDFG 2007; Kennedy 2009).…”
mentioning
confidence: 99%